2022
DOI: 10.3390/app12136384
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Profiling of Limonium vulgare Mill. Using UHPLC-DAD-ESI/MS2 and GC-MS Analysis

Abstract: Limonium vulgare Mill. is a plant growing widely in harsh environments, such as salt marshes, for which a chemical profile is still unknown, although some interesting bioactivities were already reported. So, this halophyte chemical profile must be established to find the possible bioactive compounds, valorize the species, and contribute to the salt marsh’s exploitation. This work set the chemical profile of L. vulgare’s aerial parts (leaves and inflorescences) using UHPLC-DAD-ESI/MS2 and GC-MS analysis. The li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Two types of β-myrcene appeared in the non-added samples, which were speculated by MS according to the consistent characteristic peaks. However, due to the significant difference in retention time between the two types, it indicated that the two molecules may be isomers (Carius et al, 2022;Rodríguez-Pérez et al, 2013), which lead to different affinity between gas molecules and the solid phase of the column. The retention time and characteristic peaks of β-myrcene in the FHB sample were basically the same as those in the sample of non-added, so they were the same substance in molecular structure.…”
Section: Discussionmentioning
confidence: 99%
“…Two types of β-myrcene appeared in the non-added samples, which were speculated by MS according to the consistent characteristic peaks. However, due to the significant difference in retention time between the two types, it indicated that the two molecules may be isomers (Carius et al, 2022;Rodríguez-Pérez et al, 2013), which lead to different affinity between gas molecules and the solid phase of the column. The retention time and characteristic peaks of β-myrcene in the FHB sample were basically the same as those in the sample of non-added, so they were the same substance in molecular structure.…”
Section: Discussionmentioning
confidence: 99%
“…However, since the specific conditions of particular saline habitat cause the specific metabolic response of plant species, various factors must be considered [40]. In the most recent study, Carius et al [41] analyzed the chemical profile of aerial parts of L. vulgare collected in Portugal and demonstrated a richness in polyphenolic compounds, but with differences among plant parts and stage of development. Additionally, investigation of antioxidant activities demonstrated variability among the Limonium species in relation to the environmental conditions of their natural biotopes, whereas when comparing eight Limonium species from Tunisia including L. boitardii, L. delicatulum, L. densiflorum, L. ferulaceum, L. spathulatum, L. tunetanum, L. virgatum, and L. vulgare, species L. vulgare was the one with the highest antioxidant capacity [42].…”
Section: Antioxidant Activitymentioning
confidence: 99%